Influence of Bacillus subtilis on soil microbiocenosis - Pysarenko, Pavlo; Samojlik, Maryna; Galytska, Maryna; Tsova, Yuriy; Mostoviak, Ivan (Ecological Questions, 2023)
The peculiarities of the formation and functioning of the microbial coenosis of podzolized chernozem soil and the intensity of soil-biological processes when using probiotic preparations in different concentrations containing Bacillus subtilis were studied. Probiotic preparations were applied to the soil in different concentrations and doses in separate areas, and the viability of the soil microbial coenosis of agricultural land was assessed in the spring and autumn periods on the 15th and 30th days after the application of the mixtures. The soil without any substances was considered a control option. The analysis of the coefficients of mineralization - immobilization, oligotrophicity and pedotrophicity determined that the use of probiotics helps to increase the content of nutrients in the soil for various ecological and trophic groups of microorganisms, showed that the best result for the functioning of the microbial coenosis of podzolic chernozem soil is observed when using a probiotic in a dilution of 1:10 in a dose of 100 l ha-1. Thus, the use of probiotics in a dilution of 1:10 at a dose of 100 l ha-1 can be used as an environmentally friendly fertilizer in organic farming, which will improve the biological parameters of the soil